گھریلو تشدد (نشوز وضرب) سے متعلق قرآنی نصوص کی عصری تعبیرات: تجزیاتی مطالعہ : Modern Interpretations of Qur’anic Texts on Domestic Violence (Nushūz and Ḍarb): An Analytical Study - Zeeshan Sarwar,; Prof. Dr Shah Mohyuddin Hashmi, (Al Manhal Research Journal, 2025)
The Qur’an addresses various aspects of marital relations, including the mutual rights and duties of spouses and the framework for maintaining harmony within family life. Within this thematic domain, the concepts of nushūz (marital discord) and ḍarb (commonly understood as “striking”) have long remained among the most debated and contested issues in discussions on gender in Islamic thought. Classical exegetes and jurists have presented diverse interpretations regarding the meanings and applications of these terms. In the contemporary period, evolving notions of gender equality, human rights, and the protection of women have significantly shaped scholarly discourse, leading to renewed interpretations of the relevant Qur’anic verse. Modern scholars and thinkers—drawing on linguistic analysis, contextual readings, and the ethical spirit of the Qur’an—critically reassess traditional understandings and propose alternative interpretations. This research provides an analytical study of the terms nushūz and ḍarb, examining their linguistic roots, contextual usage, and interpretive trajectories to investigate whether Islamic teachings provide any justification for domestic violence. The study evaluates the perspectives of classical exegetes and jurists, as well as contemporary Arab scholars, Indo-Pak scholars, modern reformist thinkers, and feminist scholars. Through this comprehensive analysis, the research aims to contribute to the broader discourse on gender, ethics, and Qur’anic hermeneutics in the modern era.